MENEGUHKAN KEMBALI KONSEPSI PENDIDIKAN AKHLAK DALAM ISLAM - Wari Setiawan (STIT Islamic Village Tangerang, 2020)
In Islamic education view, education relates to good attitude or character. Cause, the students must be educated to be good man in living and life after. Education as humanizing oh human, in Islamic view, directed to get actualization of good character. In teaching context, education components might be organized and designed for its internalization. This research was conducted by the study of libraries analytic using descriptive analysis of data sources in the form of books that contain information about character education from the point of view of Islamic education. So in the end, the results of the study gave a new thought to the concept of character education in accordance with the theories of character education in the view of Islam that gives strength and opportunity to be re-implemented until internalized in every student in the scope of Islamic education in particular.